Tìm a để P(x) chia hết cho Q(x)
a) P(x) = 4x2-6x+a, Q (x) = x - 3
b) P(x) = 2x2+x+a, Q(x) = x+3
c) P(x) = x3+a.x2-4, Q(x) = x2+4x+4
d) P(x) = 2x2+a.x+1, Q(x) = x-3
e) P(x) = a.x5+5x4-9, Q(x) = x-1
f) P(x) = 6x3-x2-23x+a, Q(x) = 2x+3
g) P(x) = x3-6x2+ax-6, Q(x) = x-2
h) P(x) = x3-5x2-(a-2).x+b, Q(x)= x2-3x+2
giúp e vs ạ
a) P(x)=4x2-6x+a; Q(x)=x-3
Lấy P(x):Q(x)=4x-6 dư a+30
Vậy để P(x)⋮Q(x) ⇒ a+30=0 ⇒ a=-30
b) P(x)=2x2+x+a; Q(x)=x+3
Lấy P(x):Q(x)=2x-7 dư a+21
Vậy để P(x)⋮Q(x) ⇒ a+21=0 ⇒ a=-21
c) P(x)=x3+ax2-4; Q(x)=x2+4x+4
Lấy P(x):Q(x)=x+a-4 dư -4(a-5)x+12
Vậy để P(x)⋮Q(x) ⇒ -4(a-5)x+12=0 ⇒ (a-5)x=3
⇒ a-5 ϵ {-1;1;-3;3} (a ϵ Z)
⇒ a ϵ {4;6;2;8}
d) P(x)=2x2+ax+1; Q(x)=x-3
Lấy P(x):Q(x)=2x+a+6 dư 3a+19
Vậy để P(x)⋮Q(x) ⇒ 3a+19=0 ⇒ a=-19/3
e) P(x)=ax5+5x4-9; Q(x)=x-1
Lấy P(x):Q(x)=ax4+(a-5)x3+(a-5)x2+(a-5)x+1 dư a-4
Vậy để P(x)⋮Q(x) ⇒ a-4=0 ⇒ a=4
f) P(x)=6x3-x2-23x+a; Q(x)=2x+3
Lấy P(x):Q(x)=3x2-5x-4 dư a+12
Vậy để P(x)⋮Q(x) ⇒ a+12=0 ⇒ a=-12
g) P(x)=x3-6x2+ax-6 Q(x)=x-2
Lấy P(x):Q(x)=x2-2x+a-4 dư 2(a-4)-6
Vậy để P(x)⋮Q(x) ⇒ 2(a-4)-6=0 ⇒ a=7
Bài h có a,b bạn xem lại đề